DISTANCE-BASED TOPOLOGICAL INDICES OF THE MOLECULARSTRUCTURE OF SOME DRUGS FOR TREATING CANCER PATIENTS (FULafia Journal of Science and Technology, 2026)
Topological descriptors are key tools for analyzing the intrinsic properties of chemical graphs and nanostructures, capturing molecular symmetry through graph invariants such as vertex degree, distance, and spectrum. This study investigates vertex-distance-based indices, namely: the Wiener and Hosoya indices, for selected anticancer drugs. Using linear regression models, the indices were correlated with the drugs’ physicochemical and biological properties through a Quantitative Structure–Property Relationship (QSPR) analysis, providing insight into their linear relationships and potential applications in drug design.